2004
DOI: 10.1111/j.1365-2125.2004.02172.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bronchoprotective and bronchodilator effects of a single dose of formoterol delivered by hydrofluoroalkane and chlorofluorocarbon aerosols and dry powder in a double blind, placebo‐controlled, crossover study

Abstract: BackgroundIn response to the phasing out of chlorofluorocarbon (CFC) inhalers, a metered dose hydrofluoroalkane (HFA) formulation, Modulite (Chiesi Farmaceutici S.p.A, Parma, Italy), to be delivered with a pressurized metered dose inhaler (pM DI), has been developed. Modulite is a HFA formulation technology that has been designed to provide stable and uniform dose delivery of HFA-based formulations to enable an easy transition from CFC to HFA inhalers. ObjectivesThe aim of this study was to compare the broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Systemic exposure (AUC) to formoterol from the combination pMDI was about 20% lower than that from the formoterol DPI. In contrast, Houghton and colleagues reported similar systemic absorption of formoterol with both pMDI and DPI administration, resulting in similar systemic effects [31].…”
Section: Discussionmentioning
confidence: 89%
“…Systemic exposure (AUC) to formoterol from the combination pMDI was about 20% lower than that from the formoterol DPI. In contrast, Houghton and colleagues reported similar systemic absorption of formoterol with both pMDI and DPI administration, resulting in similar systemic effects [31].…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that the same doses of a test and reference product which have comparable systemic exposure profiles also have comparable efficacy profiles [18]. However even when significant difference in the PK profiles are present when the same doses of a test and reference product are administered, no appreciable clinical differences are observed [19,20].…”
Section: Discussionmentioning
confidence: 95%
“…Previously, IOS has been regarded as equivalent but not as an alternative to spirometry [4, 6]. Marotta et al showed that, for children at risk for asthma, IOS is a better predictor than spirometry [16].…”
Section: Discussionmentioning
confidence: 99%